In vitro differentiation of T-cells methods and protocols - Kaneko, Shin ca. 20./21. Jh (Methods in Molecular Biology, 2019)
This book explores the vital importance of T-cell differentiation in areas as wide-ranging as pathological analysis, drug development, and cell therapy of human T-cells. Focusing on human embryonic stem cells and human induced pluripotent stem cells, the chapters explore a variety of in vitro T-cell differentiation protocols as well as useful techniques to develop and evaluate cellular medicines. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, In Vitro Differentiation of T-Cells: Methods and Protocols serves as an ideal guide for researchers seeking to differentiate T-cells from pluripotent stem cells in order to achieve any number of significant goals